(untitled) (The São Paulo Journal of Mathematical Sciences, 2010)
We compute the Hochschild cohomology groups of a family of finite dimensional algebras, the toupie algebras, characterized by having the same associated ordinary quiver as canonical algebras and any admissible ideal. Moreover, we determine the simple connectedness of them and we give necessary and sufficient conditions for rigidity.